2001
DOI: 10.1046/j.1365-2222.2001.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Wasp venom immunotherapy induces a shift from IL‐4‐producing towards interferon‐gamma‐producing CD4+and CD8+T lymphocytes

Abstract: Venom immunotherapy induced a shift from IL-4-producing towards IFN-gamma-producing CD4+ as well as CD8+ T lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…At the end of a 5‐day semi‐rush VIT, there was a significant decrease in the percentages of IL‐4‐producing CD4 + and CD8 + T cells, compared with cytokine‐producing cells before VIT. After 6 months of VIT, a shift from IL‐4‐producing towards IFN‐γ‐producing CD4 + and CD8 + T lymphocytes has been reported previously, in experiments in which Treg cells have not been intensely studied [59]. During bee VIT, IL‐10 serum levels increase from the second day of the build‐up phase [56].…”
Section: Introductionmentioning
confidence: 71%
“…At the end of a 5‐day semi‐rush VIT, there was a significant decrease in the percentages of IL‐4‐producing CD4 + and CD8 + T cells, compared with cytokine‐producing cells before VIT. After 6 months of VIT, a shift from IL‐4‐producing towards IFN‐γ‐producing CD4 + and CD8 + T lymphocytes has been reported previously, in experiments in which Treg cells have not been intensely studied [59]. During bee VIT, IL‐10 serum levels increase from the second day of the build‐up phase [56].…”
Section: Introductionmentioning
confidence: 71%
“…In particular, a shift in cytokine responses from a Th2 to a Th1 pattern was demonstrated during rush VIT using both HB [45] and YJ venom [46]. Regarding T-reg, a recent study found an elevated IL-10 production by CD3(+) T cells few hours after rush VIT [47]. In our study, patients were treated with aqueous extracts of Hymenoptera venom during the incremental phase and well tolerated the shift to the maintenance dose with aluminum hydroxide-adsorbed extracts, confirming previous data [32, 48].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (Schuerwegh et al, 2001), isolated uterine lymphocyte cells were stained for 30 min in the dark at room temperature with 1 mL of specific monoclonal antibodies directed against T-cell surface markers, including APC-conjugated anti-CD3 (553066, BD Biosciences, San Diego, CA), FITC-conjugated anti-CD4 (553046, BD Biosciences, San Diego, CA), and PEconjugated anti-CD8 (553032, BD Biosciences, San Diego, CA). Next, the lymphocytes were washed with 0.2 mL PBS and centrifuged at 500 Â g for 5 min (three times).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%